Pengaruh Kepemimpinan Transformasional terhadap Organizational Citizenship Behavior Pada PT Ramayana Lestari Sentosa Tbk - Ahmad Ridha; Andi Batary Citta (Fakultas Ilmu Pendidikan Universitas Pahlawan Tuanku Tambusai, 2026)
This study aims to analyze the influence of transformational leadership on Organizational Citizenship Behavior (OCB) among contract employees at PT Ramayana Lestari Sentosa Tbk, Makassar. The study used a quantitative approach with a correlation-causality approach. The study population was all contract employees, with a total sampling technique, resulting in a sample size equal to the population, namely 51 employees. The research instrument was a psychological scale developed based on the theory of Bass and Avolio for the transformational leadership variable, and the theory of Organ, Podsakoff, and MacKenzie for the OCB variable. The results showed that transformational leadership positively influenced employee OCB. The higher the implementation of transformational leadership, the higher the tendency for employees to display extra-role behaviors that support organizational effectiveness. Employee perceptions of transformational leadership were high, as reflected in aspects of idealized influence, inspirational motivation, intellectual stimulation, and individual attention. Similarly, employee OCB levels were also high, as demonstrated through the dimensions of altruism, conscientiousness, sportsmanship, courtesy, and civic virtue. These findings reinforce transformational leadership theory, which emphasizes the importance of leaders in shaping positive employee behavior. Practically, the results of this study provide implications for companies to continue to develop transformational leadership styles as a strategy to improve employee OCB behavior, so that it can support the achievement of organizational goals more effectively.